2016
DOI: 10.1111/ajad.12349
|View full text |Cite
|
Sign up to set email alerts
|

Medication‐assisted treatment for hospitalized patients with intravenous‐drug‐use related infective endocarditis

Abstract: The study provides preliminary support of engaging hospitalized IDU-IE patients to initiate MAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 14 publications
1
35
1
Order By: Relevance
“…As previously elaborated in a case-series for IDU-IE among PUID, their hospitalization is an important but often missed window of opportunity for medicationassisted therapy initiation. 11 These findings are in line with prior studies suggesting that PUID hospitalized for IDU-IE receive suboptimal addiction treatment. 12 An important finding in our study is the underutilization of transition to drug rehabilitation facilities.…”
Section: Discussionsupporting
confidence: 87%
“…As previously elaborated in a case-series for IDU-IE among PUID, their hospitalization is an important but often missed window of opportunity for medicationassisted therapy initiation. 11 These findings are in line with prior studies suggesting that PUID hospitalized for IDU-IE receive suboptimal addiction treatment. 12 An important finding in our study is the underutilization of transition to drug rehabilitation facilities.…”
Section: Discussionsupporting
confidence: 87%
“…However, there have been limited studies demonstrating the impact of OAT on the risk of deep tissue infections. Interestingly, other studies examining deep tissue infections among injection drug users call for enhanced access to addiction treatment to address the underlying causes of such infections [26,90,91]. Additional studies are needed to support our findings.…”
Section: Plos Onementioning
confidence: 63%
“…Prior studies have shown that hospitalizations represent important opportunities to initiate treatment and link to ongoing treatment after discharge [ 31–33 ]. Even though their hospital admission was not for the purpose of seeking addiction treatment, PWID often accept addiction treatment offered in the hospital [ 31 , 34 ]. In a study of 29 hospitalized patients with IDU-related endocarditis who were offered addiction psychiatry consultation, the majority (62%) accepted and initiated buprenorphine or methadone treatment during hospital admission [ 34 ].…”
Section: Discussionmentioning
confidence: 99%